Characterising yeast isolates from Malaysia towards the development of alternative heterologous protein expression system - Douglas Law Sie Nguong; Lim, Yao Jun; Nor Idaya Yatim; Sheila Nathan; Abdul Munir Abdul Murad; Nor Muhammad Mahadi; Farah Diba Abu Bakar (Universiti Kebangsaan Malaysia, 2011)
Yeasts with GRAS (Generally Regarded as Safe) status are commonly used as hosts for heterologous protein production. Yeasts are suitable expression hosts as they have been extensively characterised genetically. The objective of this project was to isolate yeasts from Malaysian food sources and subsequently to develop these as alternative hosts for heterologous protein production. Yeasts were isolated from Malaysian traditional fermented food namely ‘tapai’, ‘tuak’ and ‘ragi’. A total of 23 isolates were obtained and subjected to molecular identification by amplification and sequencing of the universally conserved ribosomal internal transcribed spacer (ITS), 26S rDNA and 18S rDNA sequences. We identified three species of yeasts, Saccharomyces cerevisiae, Hanseniaspora guilliermondii and Pichia anomala, which have a long tradition of usage in food production and have no adverse effects on humans. To test the feasibility of the yeasts as heterologous expression hosts, we have constructed an integrative vector, p1926Zeo containing the yeast 26S rDNA and Zeocin® resistance cassette. The p1926Zeo vector was linearised and transformed into both P. anomala and H. guilliermondii isolates via electroporation. Both hosts were successfully transformed at a relatively high efficiency. The transformants obtained had a growth profile similar to the respective wild type, indicating that integration of the plasmids into the host chromosome did not affect growth. These transformants were stable as they exhibited resistance to Zeocin even after 20 generations. Thus, both P. anomala and H. guilliermondii isolates exhibited the potential to be further developed as alternative heterologous protein expression hosts.